Suez and Sterling, 1956 - Adam Klug; Gregor W. Smith (Queen's University, Department of Economics, 1999)
Daily data on spot and forward dollar/sterling exchange rates and on Britain's foreign exchange reserves are used to reassess the financial history of the 1956 Suez crisis. We find that support of sterling at its Bretton Woods lower bound lost credibility as early as July. Reserve losses also are consistent with an exchange rate crisis. We provide the first econometric study of foreign exchange market intervention in the pre-convertibility phase of the Bretton Woods system. The Bank of England's interventions reacted strongly both to official sterling and to the transferable sterling market in New York, which suggests that convertibility was a central goal of policy.
Keywords: F31; N24; 330; Suez crisis; Bretton Woods system; foreign exchange market intervention